2016
DOI: 10.1007/s10238-016-0423-4
|View full text |Cite
|
Sign up to set email alerts
|

Interferon lambda polymorphisms associate with body iron indices and hepatic expression of interferon-responsive long non-coding RNA in chronic hepatitis C

Abstract: Single nucleotide polymorphisms (SNPs) within DNA region containing interferon lambda 3 (IFNL3) and IFNL4 genes are prognostic factors of treatment response in chronic hepatitis C (CHC). Iron overload, frequently diagnosed in CHC, is associated with unfavorable disease course and a risk of carcinogenesis. Its etiology and relationship with the immune response in CHC are not fully explained. Our aim was to determine whether IFNL polymorphisms in CHC patients associate with body iron indices, and whether they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Hepcidin expression during HCV infection is complicated by the effect of genetic factors. These factors have been shown to predispose patients with HCV to a different treatment potential of anti-HCV drugs (Wróblewska et al 2017 ).…”
Section: Mechanisms Of Low Hepcidin In Liver Diseasementioning
confidence: 99%
“…Hepcidin expression during HCV infection is complicated by the effect of genetic factors. These factors have been shown to predispose patients with HCV to a different treatment potential of anti-HCV drugs (Wróblewska et al 2017 ).…”
Section: Mechanisms Of Low Hepcidin In Liver Diseasementioning
confidence: 99%
“…Recently, we have confirmed an interesting link between favorable, prognostic immune profile associated with single nucleotide polymorphism (SNP) encoding interferon lambda 3 (rs12979860 CC) with lower serum iron and ferritin, and decreased hepatic expression of hepcidin and some interferon stimulated genes in CHC patients. 24 This SNP associates with a better response to treatment with interferon and a higher chance for spontaneous HCV elimination. These observations in vivo are compatible with the results by Foka et al They may serve for better understanding of host-virus interactions and the links between virulence of HCV, iron metabolism and immune response in HCV-related disease.…”
mentioning
confidence: 99%
“…Although the precise molecular mechanism linking the rs12979860 SNP to IFN/RBV response has not been identified, its impact on immune function in response to HCV infection has been demonstrated. Additionally, there was an association of IFNL genotype with systemic iron balance, which may play a role in impacting peripheral iron status[ 37 ]. A recent paper which described clinical trial simulations in a mathematical model of RBV-induced anemia in HCV patients suggested, in contrast to our observations, that the non-CC rs12979860 patients had the least severe anemia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%